PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR PADA SISWA KELAS V SD - Mega Syamsiah; Zulfahita; Sri Mulyani (Universitas Negeri Medan, 2025)
This study aims to: (1) To determine the differences in contextual teaching and learning (CTL) models on procedural text writing skills in grade V students of SD-IT Nurul Islam Singkawang. (2) To determine how much influence the contextual teaching and learning (CTL) model has on procedural text writing skills in grade V students of SD-IT Nurul Islam Singkawang. The research used is quantitative research with a post-test only control group design. The population in this study were grade V students of SD-IT Nurul Islam Singkawang. The data collection technique used in this study was a test. The data analysis technique used was the analysis of the average, percentage and effect size. The results of the study showed that: (1) There were differences in contextual teaching and learning models on procedural text writing skills in grade V students of SD-IT Nurul Islam Singkawang, namely the experimental group obtained a score of 86 and the control group 73. (2) The influence of the contextual teaching and learning model on the skills of writing procedural texts in class V students at SD-IT Nurul Islam Singkawang is 1,625, which falls into the high criteria.